PENGARUH PENAMBAHAN ABU AMPAS TEBU DAN SUPERPLASTICIZER TERHADAP KUAT TEKAN BETON - Tisnawati Tisnawati; Dwi Kumalasari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Concrete added material is an ingredient other than a constituent of concrete added to the concrete mix, before, immediately, or during concrete stirring. Added ingredients that are mixed on the concrete mix are intended to change one or more of the concrete properties while still fresh or hardened, for example the nature of the workmanship is easier, the nature of binding faster, get more plastic fresh concrete, faster rate of strength or compressive strength which is generated larger. The added ingredients used are ashes baggase (baggase ash) and supperplasticizer, and in this study itself aims to find out how much influence the addition of bagasse ash and superplasticizer sikament NN to the compressive strength of concrete, so it can be known how the optimum percentage of bagasse ash cement that produces maximum compressive strength of concrete. Planning of concrete mixture in this research using trial method by taking 5 variation of ash bagasse, 0%, 5%, 10%, 15%, 20% from cement weight and 4 variations of superplasticizer addition that is 0%, 1% , 1.5% of the weight of cement. Testing of concrete compressive strength as much as 60 specimens carried out at the age of 28 days. Based on the result of this research, it can be concluded that maximum compressive strength value in concrete is found on ash bagasse 15% and superplasticizer 1.5% with an average compressive strength of 34,991 Mpa or an increase of 17,790%. From the results of this study, it can be concluded that the use of bagasse ash and superplasticizer can increase the compressive strength of concreteKeywords: Compressive strength, Baggase Ash, Superplasticizer.